Gugatan Perbuatan Melanggar Hukum Akibat Pencemaran Nama Baik melalui Media Elektronik terhadap Perseroan Terbatas - Anand, Ghansham; Putri, Dita Elvia Kusuma; Nugraha, Xavier (Notaire, 2024)
This article aims to analyze the systematic legal framework in terms of law enforcement against alleged defamation through electronic media. law enforcement in the event of alleged defamation through electronic media against a Limited Liability Company, considering that in the event of defamation against a Limited Liability Company, there are generally 2 (two) legal remedies that can be used. Limited Liability Company, there are generally 2 (two) legal remedies that can be used: 1) Criminal legal remedies, through a complaint as stipulated in Article 27 paragraph (3) of the ITE Law; and/or 2) Lawsuit for the unlawful act (onrechtmatige daad) due to defamation as stipulated in Article 27 paragraph (3) of the ITE Law; and/or 2) defamation regulated in Article 1372 Burgerlijk Wetboek (BW). This research is legal research with a statutory approach (statute approach), conceptual approach, and case approach. approach, and case approach. approach). The findings of this article are in the use of legal remedies and legal remedies against alleged defamation through electronic media against a Limited Liability Company, it must use legal remedies. against a Limited Liability Company, then it must use criminal legal remedies first because civil judges cannot use criminal legal remedies. criminal remedies first, because civil judges cannot seek material truth and are only bound to formal truth, so that civil judges cannot seek material truth. bound to the formal truth, so that civil case judges cannot judge whether there is assess whether or not there is defamation of a Limited Liability Company through electronic media. electronic media. The implication of this article is to resolve legal issues, related to legal vagueness regarding the systematic law enforcement order of defamation through electronic media against Limited Liability Companies. Limited Liability Company. This article is qualified, as an original article, because in Similar articles have not been discussed: 1) Qualification of PT as a legal subject that can be defamed through electronic media; and 2) electronic media; and 2) The systematic order of law enforcement against against defamation through electronic media against Limited Liability Companies. Limited Liability Company.